Slaying monsters for the feeble eaudiobook - Marie, Annette (Guild Codex: Demonized, 2020)
I'm bound to a demon. For my entire life, I avoided magic at all costs. Now, I'm responsible for a demon who wields magic more powerful than the toughest mage or sorcerer. Demons are evil. That's what my textbooks say. That's what I see. He's ruthless, he's temperamental, he's cold. But he protects me without fail. I wonder if he's hiding a heart behind his hostility. My demon is a monster. Whether he's heartless or not, my contract with him is illegal and beyond dangerous. Together, we must find a way to return him to his own world before anyone discovers our secret. If that wasn't bad enough, I've come to realize something else: My demon isn't the only monster I should be worried about. Make sure to check out the companion series, The Guild Codex: Spellbound, available now, and The Guild Codex: Warped, coauthored by Rob Jacobsen, available summer 2020.